ВОЗЕҲ САЁҲАТНОМАСИДА МАЪРИФАТПАРВАРЛИК ҒОЯЛАРИ ТАЛҚИНИ - Юнусзода, З.Ю. (SCIENCE and SOCIETY, 2017)
The article deals with the research work of Kori Rakhmatulloh Vozeh “Savoneh ul-masolik fi farosih ul-mamolik” (“Travel stories and the areas of the countries”) of the literary representative enlightener who lived and worked in the field of literature in the second half of the XIX century in Bukhara. It contains the analysis of the novel’s genre peculiarities, a conceptual content, author’s progressive views, political thoughts and realistic descriptive methods.
Keywords: travel notes; genre; a conceptual content; enlightenment views of the author; political ideas; realistic descriptive methods